PELATIHAN PENGGUNAAN GPS (GLOBAL POSITIONING SYSTEM) SEBAGAI PENGETAHUAN DALAM PEMETAAN MITIGASI BENCANA GEMPA BUMI BAGI GURU SMA N 2 DAN SMA N 3 PADANG - Yunasril Yunasril; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract: PKM Training on the Use of GPS (Global Positioning System) as Knowledge in Mapping Earthquake Disaster Mitigation for Teachers of SMA N 2 and SMA N 3 Padang aims to provide skills training on the use of GPS in mapping earthquake disaster mitigation. Problem solving is done through several stages, namely observation, provision of material, training in the use of GPS, making 2-dimensional contour maps and 3-dimensional models that are ultimately used as learning media for mapping and surveying. Based on the results of preliminary observations there has never been a training or course for teachers in SMA N 2 and SMA N 3 Padang relating to mapping and surveying, the unavailability of GPS labsheets and GPS programs, operating instructions and GPS software. Not many teaching aids and other media are found in learning, so it will greatly affect the success and completeness of learning. Teachers will find it difficult to exclude material without being supported by adequate references and learning media. In learning, media is still used as is, such as the use of analog maps and mapping techniques are still manual. Teachers are still lacking in understanding GPS, both in substantial and practical skills, due to the limited skills and infrastructure they have. Departing from these limitations, training in the use of GPS for mapping digital earthquake disaster mitigation needs to be held which is expected to later be able to better understand material about mapping with extraterrestrial measurements and be used as digital media in the learning process in the globalization and informative era. Keyword : GPS, labsheet, digital media, earthquake